Testimonianze dal mare - Pepe, Carla (Kritik. Rivista di letteratura e critica culturale, 2024)
Ischia is an island with many identities, and engage with the Genius Loci, the spirit of the place, means going back to the “natural forces” of its landscape, in relation to the stratification of its past. For of its special strategic position and safe harbours, Ischia was a protagonist in the earliest history of the Mediterranean and represents an essential mainpoint in the understanding of the dynamics of transmarine contacts in the Bronze Age, becoming a nodal point in the subsequent Greek colonisation of the West. If men navigated the Mediterranean looking for ports-landing to trade, on the same routes the imposing and shiny pelagic fish: the tuna, also “sailed” regularly since prehistoric times. Tuna fishing has been carried out on Ischia since ancient times. Tuna fisheries were located in strategic positions, which coincide with topographical punctuality with archaeological sites that dominate the coastline below, and are often connected to a double port-landing area. The sea offers illuminating evidence of its past – a sea that narrates not only trade routes and food resources, but also shipwrecks and material culture: the Archaeological Museum of Pithecusae exhibits the finds discovered by Giorgio Buchner and we can see, among others, the Cup of Nestor and the Crater of Shipwreck.